Dominance Between Plasmids Determines the Extent of Biofilm Formation - Gama, João Alves; Fredheim, Elizabeth G. Aarag; Cléon, François; Reis, Ana Maria; Zilhão, Rita; Dionisio, Francisco (Frontiers in Microbiology, 2020)
Bacterial biofilms have an impact in medical and industrial environments because they often confer protection to bacteria against harmful agents, and constitute a source from which microorganisms can disperse. Conjugative plasmids can enhance bacterial ability to form biofilms because conjugative pili act as adhesion factors. However, plasmids may interact with each other, either facilitating or inhibiting plasmid transfer. Accordingly, we asked whether effects on plasmid transfer also impacts biofilm formation. We measured biofilm formation of Escherichia coli cells harbouring two plasmid types, or when the two plasmids were present in the same population but carried in different cells. Using eleven natural isolated conjugative plasmids, we confirmed that some indeed promote biofilm formation and, importantly, that this ability is correlated with conjugative efficiency. Further we studied the effect of plasmid pairs on biofilm formation. We observed increased biofilm formation in approximately half of the combinations when both plasmids inhabited the same cell or when the plasmids were carried in different cells. Moreover, in approximately half of the combinations, independent of the co-inhabitation conditions, one of the plasmids alone determined the extent of biofilm formation – thus having a dominant effect over the other plasmid. The molecular mechanisms responsible for these interactions were not evaluated here and future research is required to elucidate them.